2005
DOI: 10.15288/jsa.2005.66.593
|View full text |Cite
|
Sign up to set email alerts
|

Fetal alcohol syndrome epidemiology in a South African community: a second study of a very high prevalence area.

Abstract: ABSTRACT. Objective: The aim of the study was to determine the prevalence and characteristics of fetal alcohol syndrome (FAS) in a second primary school cohort in a community in South Africa. Method: Active case ascertainment, two-tier screening, and Institute of Medicine assessment methodology were employed among 857 first grade pupils, most born in 1993. Characteristics of children with FAS were contrasted with characteristics of a randomly selected control group from the same classrooms. Physical growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
165
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(169 citation statements)
references
References 39 publications
4
165
0
Order By: Relevance
“…The high prevalence of FAS/PFAS in the village of Aurora is consistent with: (i) the rural-urban gradient in FAS prevalence shown in Table 2, (ii) studies that show a higher FAS/PFAS rate in children born in rural than urban areas, [1][2][3][4] and (iii) evidence that binge drinking is more prevalent in rural (20%) than urban informal (16%) and urban formal (15%) areas. [15] FASD also appears more prevalent in very isolated communities -the communities with the highest published prevalence of FAS/PFAS (Aurora and De Aar) are very isolated geographically.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The high prevalence of FAS/PFAS in the village of Aurora is consistent with: (i) the rural-urban gradient in FAS prevalence shown in Table 2, (ii) studies that show a higher FAS/PFAS rate in children born in rural than urban areas, [1][2][3][4] and (iii) evidence that binge drinking is more prevalent in rural (20%) than urban informal (16%) and urban formal (15%) areas. [15] FASD also appears more prevalent in very isolated communities -the communities with the highest published prevalence of FAS/PFAS (Aurora and De Aar) are very isolated geographically.…”
Section: Discussionsupporting
confidence: 79%
“…[1][2][3][4] Over the past decade, levels of FAS/PFAS ranging between 40.5 and 119.4 per 1 000 have been documented in several parts of these provinces. [1,4] A recent study examined the prevalence of FASD (which is a broader and less well defined group) in an area of the Western Cape, and estimated the prevalence at between 135.1 and 207.5 per 1 000.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The highest global rates of FAS and PFAS have been identified in various regions of South Africa since the mid-1980s, and most notably, in rural farming areas in the Western Cape Province (May et al, 2000(May et al, , 2007Palmer, 1985;Viljoen et al, 2005; te Water Naude, London, Pitt, & Mahomed, 1998). More recent studies, conducted in high risk areas of the Northern Cape (Urban et al, 2008) and Gauteng provinces (Viljoen, Craig, Hymbaugh, Boyle, & Blount, 2003), have also documented high rates.…”
mentioning
confidence: 99%
“…More recent studies, conducted in high risk areas of the Northern Cape (Urban et al, 2008) and Gauteng provinces (Viljoen, Craig, Hymbaugh, Boyle, & Blount, 2003), have also documented high rates. Of concern are the observed increases in the prevalence of FAS; studies among three separate cohorts of Grade 1 pupils in Western Cape province in 1997 (May et al, 2000), 1999 (Viljoen et al, 2005), and 2001 (May et al, 2007) identified rates of FAS of 40.5-46.4 per 1000; 65.2-74.2 per 1000; and 68.0-89.0 per 1000, respectively. The rate of FAS identified in an urban area of Gauteng province was 19 per 1000 (Viljoen et al, 2003), whereas a combined rate for two locations in the Northern Cape of 67.2 per 1000 was identified between 2001 and 2004 (Urban et al, 2008).…”
mentioning
confidence: 99%